Glycogen accumulation, central carbon metabolism, and aging of hematopoietic stem and progenitor cells - Poisa-Beiro, Laura; Thoma, Judith; Landry, Jonathan; Sauer, Sven; Yamamoto, Akihisa; Eckstein, Volker; Romanov, Natalie; Raffel, Simon; Hoffmann, Georg F.; Bork, Peer; Benes, Vladimir; Gavin, Anne-Claude; et al. (Scientific reports, 2020)
Inspired by recent proteomic data demonstrating the upregulation of carbon and glycogen metabolism in aging human hematopoietic stem and progenitor cells (HPCs, CD34+ cells), this report addresses whether this is caused by elevated glycolysis of the HPCs on a per cell basis, or by a subpopulation that has become more glycolytic. The average glycogen content in individual CD34+ cells from older subjects (> 50 years) was 3.5 times higher and more heterogeneous compared to younger subjects (< 35 years). Representative glycolytic enzyme activities in HPCs confirmed a significant increase in glycolysis in older subjects. The HPCs from older subjects can be fractionated into three distinct subsets with high, intermediate, and low glucose uptake (GU) capacity, while the subset with a high GU capacity could scarcely be detected in younger subjects. Thus, we conclude that upregulated glycolysis in aging HPCs is caused by the expansion of a more glycolytic HPC subset. Since single-cell RNA analysis has also demonstrated that this subpopulation is linked to myeloid differentiation and increased proliferation, isolation and mechanistic characterization of this subpopulation can be utilized to elucidate specific targets for therapeutic interventions to restore the lineage balance of aging HPCs.